Canva-based Digital Storybooks to Improve Pancasila Education Learning Outcomes for Fifth Grade of Elementary School - Damarsari, Noviana Astuti; Widodo, Susilo Tri (Indonesian Journal of Educational Research and Review, 2024)
Learning media is an important component in learning to stimulate students to learn and learning objectives can be achieved. This research aims to develop digital storybook learning media on Pancasila Education subject content that is good, effective, and quality, to support the improvement of student learning outcomes. This type of research falls into the category of research and development (R&D) by applying the Borg and Gall model.  Respondents in this study were fifth grade students with a total of 20 students. Then this research involves media experts and material experts to provide validation of the developed media. The data collection process in this study was carried out through interviews, expert validation, response questionnaires, and pretest and post-test sheets. This research resulted in, among others: digital storybooks are very feasible to use and this can be seen from the assessment obtained from learning material content experts who obtained a percentage of 90.38% (very feasible) and learning media experts obtained a percentage of 90.38% (very feasible); from the results of digital storybook responses rated very practical; digital storybooks are proven to be effective based on the results of the N-gain test, where there is an increase in the average value of the post-test with the average value of the pretest. This shows that digital storybook learning media is very feasible to use and can improve the learning outcomes of fifth grade students on the content of Pancasila Education.